Mixed chimerism and graft loss in pediatric recipients of an alemtuzumab‐based reduced‐intensity conditioning regimen for non‐malignant disease. Issue 10 (17th June 2014) - Oshrine, Benjamin R.; Olson, Timothy S.; Bunin, Nancy
Abstract Background Reduced‐intensity conditioning (RIC) regimens can mitigate the toxicity of hematopoietic cell transplantation (HCT) in children with non‐malignant diseases, but are associated with increased risk for post‐transplant mixed donor/recipient chimerism (MC) and/or graft loss (GL). Intervention with donor lymphocytes or stem cell boosts (DLI/boost) may be necessary, but there is limited information about timing and results of intervention. Procedure We retrospectively evaluated 31 consecutive pediatric recipients of an alemtuzumab‐based RIC HCT at the Children's Hospital of Philadelphia from May 2007 to December 2012 to determine the incidence of MC, GL, and use of DLI/boost. All patients received alemtuzumab with either fludarabine (150 mg/m2)/melphalan (140 mg/m2) (n = 30) or fludarabine/busulfan (n = 1), and unmanipulated marrow grafts from related (48%) or matched unrelated (52%) donors. Results Of surviving patients, 67% and 44% displayed MC and MC with ≤80% donor contribution (MC ≤ 80%), respectively. Rates of MC, MC ≤ 80%, DLI/boost, and GL were significantly higher in recipients of proximal/intermediate (100%, 73%, 46%, and 46%, respectively) compared to distal alemtuzumab (44%, 25%, 6%, and 6%, respectively). Event‐free and overall survival was significantly lower in HLH compared with non‐HLH patients. Twenty percent of patients required DLI/boost, and DLI/boost did not affect the incidence of GL. Conclusions RIC with proximal/intermediate alemtuzumab is associated with high rates of MC, need for DLI/boost, and GL. Pediatr Blood Cancer 2014; 61:1852–1859. © 2014 Wiley Periodicals, Inc.